(untitled) (Konferensiyalar | Conferences, 2024)
This article discusses the conceptual aspects related to the implementation of training. Methods using innovative pedagogical technologies in teaching computer science include calculated. The paper presents an overview of the scientific and pedagogical literature on the study of the CLIL method. In addition, the authors present an analysis of an experiment conducted with teachers, students and undergraduates of the Department of Physics and IT, a sample lesson plan using CLIL technology is presented, conducted for 1st year students of the educational program 6B01503 - "Training of computer science teachers" and 1st year undergraduates of the educational program 7M01503 - "Teacher training computer Science” at Dulaty University in Kazakhstan.